The Role of Digital Marketing in Increasing The Competitiveness of Msmes in The Era of The Industrial Revolution 5.0 - Hidayat, Agus Rohmat; Wahyuni, Ani; Fitriani, Renita; Putra, Rifky Pratama; Supandji, Wahyu (Jurnal Ekonomi Teknologi dan Bisnis (JETBIS), 2025)
The Industrial Revolution 5.0 has changed the global business paradigm, especially for Micro, Small, and Medium Enterprises (MSMEs) in facing increasingly complex competitive challenges. This research aims to analyze the role of digital marketing in increasing the competitiveness of MSMEs in the era of the Industrial Revolution 5.0. The research method uses a quantitative approach with survey techniques on 385 MSMEs in the Greater Jakarta area that have implemented digital marketing strategies. Data collection was conducted using a structured questionnaire that had been validated with a Cronbach's Alpha value of 0.892. Data analysis was conducted using Structural Equation Modeling (SEM) with AMOS 24.0 software. The results of the study show that digital marketing has a positive and significant effect on the competitiveness of MSMEs with a path coefficient value of 0.784 (p<0.001). The most influential digital marketing indicator was social media marketing (B=0.856), followed by search engine optimization (B=0.743), and content marketing (B=0.692). The competitiveness of MSMEs increased significantly through increased operational efficiency (34.2%), market expansion (41.7%), and product innovation (28.9%). This research makes a theoretical contribution to the development of an integrated digital marketing framework model for MSMEs and practical implications for the development of MSME empowerment policies in the digital era.